2021
DOI: 10.4103/jhrs.jhrs_173_21
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte cryopreservation - current scenario and future perspectives: A narrative review

Abstract: Oocyte cryopreservation is a boon for women undergoing assisted reproductive technology. With the evolution in the technique of cryopreservation over the last three decades, there has been an exponential rise in the number of oocyte cryopreservation cycles for diverse indications. Apart from cancer patients, it has also been promoted as a mode of fertility insurance to overcome the age-related decline in fertility as well as post-surgical decline following endometriosis surgery. The objective of the review is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…Recent publications reported that survival rate after cryopreservation was increased recent years, which confirms the influence of methodological approaches to female gamete cryopreservation provided by optimal ART (Pai et al, 2021). The turning point in the improvement of oocyte cryopreservation methods was the use of vitrification (Kuleshova et al, 1999).…”
Section: Cryotechnology As the Basis For Preserving Reproductive Pote...mentioning
confidence: 75%
“…Recent publications reported that survival rate after cryopreservation was increased recent years, which confirms the influence of methodological approaches to female gamete cryopreservation provided by optimal ART (Pai et al, 2021). The turning point in the improvement of oocyte cryopreservation methods was the use of vitrification (Kuleshova et al, 1999).…”
Section: Cryotechnology As the Basis For Preserving Reproductive Pote...mentioning
confidence: 75%
“…Medical reasons include mainly sickle cell anemia, severe endometriosis, diminished ovarian reserve, autoimmune diseases, and ovarian insufficiency risk due to genetic conditions such as the Fragile X premutation, and Turner syndrome ( 4 ). Other reasons are the X chromosome deletion and patients that have undergone gender diversity as transgender with affected fertility status ( 5 ). Practically, all the concerns regarding embryo cryopreservation, such as ethical, legal, and religious can be challenged by the oocyte cryobanking choice.…”
Section: Routinely Applied Assisted Reproductive Technologies For Fer...mentioning
confidence: 99%
“…For instance, at first, FP in patients undergoing gonadotoxic treatments is either the retrieval of oocytes (preferably mature) and spermatozoa from ejaculation or surgically recovered before cancer therapy treatment, or alternatively, the cryopreservation of embryos after an IVF cycle, as reported in the guidelines applied recently ( 3 , 220 ). In addition, oocyte cryopreservation has been extensively used and recommended for social freezing reasons, today referred to as “planned oocyte cryopreservation”, and for the establishment of donor egg banks ( 5 , 220 , 221 ).…”
Section: Accessibility Considerations To Fertility Preservation: Rece...mentioning
confidence: 99%
“…On the other hand, the embryo contain genetic material from both maternal and paternal sides. Compared to sperm, the larger size of oocytes and embryos reduces their cryotolerance (Pai et al, 2021). As oocytes and embryos share similarities in freezing sensitivity, the methods to modify their lipid compositions are discussed together.…”
Section: Current Status Of Oocyte and Embryo Cryopreservationmentioning
confidence: 99%